P5 Acute β-adrenergic stimulation or perfusion with a camp analogue results in immediate and sustained inhibition of mitochondrial permeability transition pore opening. (21st March 2018) - Khaliulin, I; Lewis, MJ; Halestrap, AP; Suleiman, MS
Abstract : Background: Ischaemia/reperfusion (I/R) injury is mediated by opening of the mitochondrial permeability transition pore (MPTP). Experimental studies have shown that a variety of interventions, including ischaemic preconditioning (IP), protect the heart by inhibiting MPTP during reperfusion. Interestingly, we and others have shown that IP has no inhibitory effect on MPTP prior to ischaemia. We have recently shown that acute and transient perfusion of hearts with cell-permeable cAMP analogue confers marked protection against I/R. However, whether this treatment affects MPTP opening is not presently known. The aim of this work was to address this issue. Methods: Isolated Langendorff-perfused rat hearts were perfused with either 0.2 µM of the β-adrenergic receptor agonist isoprenaline (to increase endogenous level of cAMP) for 3 min, or with 7.5 µM of the cell-permeable cAMP analogue 8-Br-cAMP-AM (8-Br) for 5 min. Mitochondria were isolated immediately after the treatment. Additional hearts were treated with either intervention and exposed to global ischaemia followed by reperfusion. Mitochondria were isolated from these hearts after 5 min of reperfusion. MPTP opening was assessed using Ca2+-induced mitochondria swelling assay or by evaluation of Ca2 +retention by mitochondria. Results: Both Iso and 8-Br inhibited MPTP opening immediately after the treatment. This inhibitory effect of MPTP opening was also observed at the beginning of reperfusion. Conclusion: In contrast to IP, acute elevation of cAMP level in myocardium either by Iso or 8-Br is associated with desensitisation of MPTP to Ca2+ retention this effect is maintained during I/R.